1999
DOI: 10.1161/01.atv.19.11.2591
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an E-box–Dependent cis Element in the Smooth Muscle α-Actin Promoter

Abstract: Abstract-Identification of the regulators of smooth muscle specific gene expression is critical for understanding smooth muscle cell (SMC) differentiation and the alterations in SMC phenotype seen in vascular diseases. Previous studies have identified that a 2-bp mutation in a conserved cis-acting element (TGTTTATC) in the promoter of the chicken smooth muscle (SM) ␣-actin gene abolished nuclear factor binding and decreased transcriptional activity of a 271-bp SM ␣-actin promoter fragment when transfected into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…As a readout of transcriptional activity, the smooth muscle alpha actin (SMaA) promoter, which has previously been shown to be activated by E12, in an E-box dependent manner, was used9, 23. As anticipated, transfection of E12 resulted in activation of the SMaA promoter, an effect which was inhibited by Id3105A in a concentration-dependent manner.…”
Section: Resultsmentioning
confidence: 86%
“…As a readout of transcriptional activity, the smooth muscle alpha actin (SMaA) promoter, which has previously been shown to be activated by E12, in an E-box dependent manner, was used9, 23. As anticipated, transfection of E12 resulted in activation of the SMaA promoter, an effect which was inhibited by Id3105A in a concentration-dependent manner.…”
Section: Resultsmentioning
confidence: 86%
“…Four independent experiments were carried out. Experiments were normalized to total protein as because we and others have observed that viral promoters interfere with SM differentiation-marker promoter responsiveness due to interactions with CArG boxes present in these promoters (37). Data were analyzed using Student's t test, and differences were considered significant for p Ͻ 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the ␣-SMA promoter of different species contains a number of highly conserved regions with consensus binding motifs for transcription factors. The 5Ј-flanking sequence upstream of the TATA box contains several cis-acting elements including two different CC(A/T-rich) 6 GG (CArG) boxes (named A and B), a MCAT motif, an E box, a TGF-␤1 control element, a TGF-␤1 hypersensitivity region, and a conserved TGTTTATC sequence (5,17,19,25,28,35). Recent studies indicate that different regulatory mechanisms induce ␣-SMA promoter activity in renal epithelial cells that convert to myofibroblasts during EMT (12,54,62).…”
mentioning
confidence: 99%